Evaluation of the National Values Construction Program for National Resilience Institute Republic of Indonesia (LEMHANNAS RI) - Yuhastihar; Hamidah; Madhakomala (Bright Institute, 2022)
The Program for Strengthening National Values was established by Presidential Regulation Number 67 of 2007 addressing Lemhannas RI. This study's goal is to assess Lemhannas RI's national values building initiative from 2007. This research used the CIPP program assessment paradigm and included observation, interviews, questionnaires, Focus Group Discussions, and document examination. The research included 220 national values strengthening graduates, 4 (four) RI Lemhannas officials who implemented the stabilization program, 3 (three) Lemhannas RI Professional Staff who became resource people for the stabilization program, and 10 (ten) alumni. The findings of the context assessment indicated that Lemhannas RI's implementation of the Program for the Consolidation of National Values had a strong legal foundation, clear and realistic aims and objectives, and significant community needs. For example, inadequate cost support, inadequate curriculum support, inadequate human resource (HR) support, inadequate infrastructure support, and inadequate recruitment participants were found in the Input evaluation. The program may be carried out as intended, and the process monitoring and assessment can offer an overview of quantifiable outcomes. The effect of the strengthening program on alumni is excellent, as shown by changes in attitudes, motives, and actions.